Initiation of Failure for Masonry Subject to In-Plane Loads through Micromechanics - Berardi, V. P. (Modelling and Simulation in Engineering, 2016)
A micromechanical procedure is used in order to evaluate the initiation of damage and failure of masonry with in-plane loads. Masonry material is viewed as a composite with periodic microstructure and, therefore, a unit cell with suitable boundary conditions is assumed as a representative volume element of the masonry. The finite element method is used to determine the average stress on the unit cell corresponding to a given average strain prescribed on the unit cell. Finally, critical curves representing the initiation of damage and failure in both clay brick masonry and adobe masonry are provided.